The critique of the state - Bartelson, Jens (Cambridge University Press, 2001)
The concept of the state has been central to the study of politics and society. Jens Bartelson examines the history of the concept, and argues that the state has largely been taken for granted as the embodiment of authority, rather than analyzed itself. He sees the state as a historically limited phenomenon, and argues that this explains the way political scientists have framed the subject they study. This book will appeal to political and social theorists, as well as philosophers of social science.